CHARACTERISTIC FEATURES OF ENTREPRENEURIAL ACTIVITY IN UKRAINE DURING THE WAR - PAVLOVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Today, all segments of Ukrainian society are facing tough challenges. No one could have predicted that in the 21st century, the world would once again face the kind of brutality that every Ukrainian is experiencing. Business activity is significant for the country’s economic stability during the war. Anyone who works, creates jobs, volunteers, or contributes to the state budget becomes a reliable rear guard for Ukraine’s defenders, defending our land from the aggressor. Ukraine is going through one of the most challenging periods in its history, affecting everyone morally and financially. Planning for the future has become difficult as uncertainty reigns supreme. Many people live for one day. However, it is essential not to lose faith and continue to work hard to prove that the truth has always been and remains on our side. Only by working together can we win. The COVID-19 pandemic has already dealt a significant blow to the business sector, forcing many players to leave the market. The strongest survived the test, while the weakest failed to withstand the pressure of quarantine restrictions and economic difficulties. Today, businesses that have survived the pandemic have valuable crisis management experience that helps them respond more effectively to current challenges and make operational decisions. The war caused enormous losses to entrepreneurs. Some went bankrupt, others lost many years of achievements due to the fighting, and some were forced to relocate their businesses abroad in search of new markets. In the 21st century, entrepreneurship plays a key role in sustaining economic activity. In the context of the war in Ukraine, doing business is complicated by the lack of skilled labor, financial difficulties, and psychological pressure. In these challenging times, the importance of collaboration becomes even more evident, uniting us in our shared goal of overcoming these obstacles. Nevertheless, supporting economic activity, creating jobs, paying taxes, and volunteering remain critical to ensuring a strong home front for the Ukrainian army. To summarize, Ukrainian entrepreneurs have suffered and continue to suffer significant losses, with many losing their businesses due to the hostilities. Many people have lost their long-standing developments, offices, and teams because of shelling, occupation, and other consequences of the war. However, with the proper support and investment, these businesses can recover and contribute to Ukraine’s overall economic growth and stability. This is where international support and investment play a crucial role, and we urge potential investors and policymakers to consider the opportunities in Ukraine’s post-war economy.